Prevalence and Risk Factors Associated with Symptomatic Dry Eye in Nurses in Palestine During the COVID-19 Pandemic - Riyad Allayed MSN; Ahmad Ayed MSN, PhD; Imad Fashafsheh PhD (SAGE Publishing, 2022)
Introduction Working in closed wards at hospitals during night-time shifts and using electronic health records may raise the risk of dry eye disease in nurses. Objective The purpose of the current study was to assess the prevalence and associated factors of dry eye disease among hospital nurses in the North West Bank, Palestine. Methods A descriptive cross-sectional study. The study included 300 nurses who work at hospitals in the North West Bank, Palestine. The Ocular Surface Disease Index (OSDI) questionnaire on dry eye disease was used to estimate the prevalence of symptomatic dry eye disease. Results The percentage of dry eye disease prevalence among study participants was 62% with an OSDI score of >13 (mild to moderate and severe OSDI status). Nurses who wore contact lenses worked during the night-time, and worked in the intensive care unit were more likely to report significantly higher OSDI scores ( p  < .05). Moreover, gender, smoking, and computer use were not statistically associated with dry eye disease ( p  > .05). Conclusion Symptomatic dry eye disease is one of the most common ocular diseases among hospital nurses in Palestine.